Authenticity: Effective emotional labor strategies on teaching efficacy of university teachers in China. - Jiuhua Zheng; Yuqing Geng; Juan Gao; Qinjun Xiang (PLoS ONE)
Based on the job demands-resources model, this study explored the relationships among emotional labor strategies, job demands of teaching, job resources, and teaching efficacy for university teachers. The results, based on a sample of 316 university teachers from China, showed that the teachers preferred to convey authenticity by expressing deep acting and naturally felt emotion. Furthermore, deep acting and naturally felt emotions were found to have a significant positive effect on teaching efficacy, whereas surface acting did not have any significant relationship with teaching efficacy. As organizational variables, job demands significantly positively affected surface acting, deep acting, and naturally felt emotion. In contrast, job resources positively affected surface and deep acting, but no significant relationship with naturally felt emotions was found. These results highlight that university teachers from China could benefit from adopting authentic emotional labor strategies, specifically deep acting and naturally felt emotions, as the most effective strategies in teaching. Based on the above findings, this paper concludes with recommendations for university administrators to alleviate the emotional labor of college faculty. For example, universities should pay more attention to teachers' emotional state, provide resources to support them, and give more space and support to college teachers in teaching.